Scan QR code or get instant email to install app

Skip to content
#
Solve for x.

3(x + 1) = 5(x − 2) + 7

### Related Information

Question:

3(x + 1) = 5(x − 2) + 7

A
3

explanation

Begin by distributing the 3 and the 5 through their respective parentheses, then combine like terms on each side of the equal sign:

3(x + 1) = 5(x − 2) + 7

3x + 3 = 5x − 10 + 7

3x + 3 = 5x − 3

3x + 6 = 5x

6 = 2x

3 = x

Visit our website to practice asvab test for other ASVAB topics now!

Comments

Frankie Felix

1 year ago

Very easy to learn with this app

The Panter77

1 year ago

Great app it help me a lot

PYROROA 333

1 year ago

Pretty good for learning basic stuff. Just wish the equation would change up so you don't just remember the answer.